PEMAHAMAN, PELAKSANAAN ZAKAT HASIL SAWIT OLEH PARA PETANI DI KECAMATAN ANGKOLA SANGKUNUR KABUPATEN TAPANULI SELATAN - Damri Batubara (Institut agama islam negeri Padangsidimpuan, 2020)
Zakat is an obligation that must be fulfilled by Muslims if their properties and conditions are met. Based on Allah's commands, the zakat of fruits and plants has been explained in general in the Koran and also in the words of the Messenger of Allah. Strengthened by the opinion of the scholars who stated that all income from any business must be tamed, including the results of palm oil alms. Oil palm charity when traded (sold) is equated with trade charity. The reality that occurs on the ground, many oil palm farmers do not tithe. As for zakat, which is not in accordance with zakat management procedures. So that there are many features in the zakat procedure, especially zakat on palm products. Therefore it is necessary to know the actual understanding and implementation of zakat on palm oil. So that the oil palm farmers are directed in the irimplementation.